Decision Making to Strive Inclusive Education in Indonesia: Literature Study on the Role of Government, Schools, and Society - Teguh Trianung Djoko Susanto; Nuron Jamil, Soraya; Muhammad Zulfakar Pratama; Fatihatul Karomah; Fyfty Ayu Lestari Kosam (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Implementing inclusive education requires collaboration and involvement of various stakeholders, including the government, schools, and the community. However, the implementation of inclusive education still faces various obstacles. By using literature studies, this research analyzes the actual role of stakeholders such as the government, schools, and society in implementing inclusive education in Indonesia. The research results state that the government is responsible for allocating an adequate budget for the implementation of inclusive education, such as providing accessible infrastructure, teacher training, and procuring supporting resources. Schools are responsible for creating a learning environment that is friendly, inclusive, and respectful of diversity, by providing accessible facilities, flexible learning methods, and accommodations according to the specific needs of each student. The community plays a role in increasing awareness about the importance of inclusive education through campaigns and social activities, providing moral and social support to students with special needs, being involved in school and related community activities, and providing input to the government and schools.